Single molecule investigation of the structural aspects and mass transport dynamics of mesoporous silica nanopores - Kumarasinghe, Ruwandi (Kansas State University, 2019)
This dissertation describes single-molecule tracking (SMT) studies for the quantitative characterization of one-dimensional (1D) solvent-filled surfactant-templated mesoporous silica (STMS) materials and other nanostructured materials, such as double-stranded DNA. SMT permits the simultaneous and quantitative assessment of the nanoscale and microscale morphologies and mass-transport properties of the materials with nanometer-scale spatial resolution. The efficiency and selectivity of catalytic reactions and chemical separations occurring in liquid-filled mesoporous materials are governed by the translational and orientational mobilities and surface interactions of the incorporated reagents and analytes. Polarization dependent SMT results demonstrate that the dye molecules used as probes of materials nanostructure are tightly confined within the one-dimensional (1D) pores of surfactant-templated mesoporous silica films. Spectroscopic single molecule tracking (sSMT) data reveal that the hydrophobic probe dyes are confined within nonpolar regions of the nanomaterials For this dissertation, surfactant templated mesoporous silica films were prepared by the spin coating of acid catalyzed tetramethoxysilane (TMOS)-based silica sols on glass substrates in the presence of Cetyltrimethylammonium bromide (CTAB). Cylindrical CTAB micelles formed during evaporation of the solvent acted as a structure directing template, forming nanometer-sized one-dimensional pores within the silica films. SMT experiments were performed using a wide-field fluorescence microscope that was sufficiently sensitive to allow detection of the fluorescence from individual dye molecules. A series of perylene diimide (PDI) dyes was employed for basic structural characterization of the silica materials. Single molecule fluorescence was recorded in the form of fluorescence videos. These videos revealed the presence of immobile dye molecules, along with those diffusing in one and two dimensions (1D and 2D). The 1D diffusing molecules provided basic evidence for the confinement mass transport of the dye molecules within the silica mesopores. Spectroscopic single molecule tracking (sSMT) studies served as an extension of basic SMT experiments and were employed to determine the location of the molecules. The polarity sensitive dye Nile Red (NR) was employed in these studies. It exhibits 1D diffusion, consistent with its confinement to the cylindrical pores, as was also the case for the PDI dyes. The sSMT data revealed that the majority of NR molecules were found in nonpolar environments having polarities similar to that of n-hexane. Single molecule emission polarization (SMEP) measurements were employed to explore the orientational confinement of the dyes. The results of these experiments demonstrated that the PDI and NR molecules diffuse with their long axes aligned parallel to the long axis of the pores. All of the dyes employed were found to be orientationally confined to ∼1 nm diameter pathways within the pores. The diffusion coefficient for the dyes was also shown to be ∼10³ -fold smaller than in bulk solution. The results of the NR studies demonstrate that the dye molecules were confined to the hydrophobic cores of the micelles, and provide support for the conclusion that the PDI dyes are similarly confined. These studies afford an enhanced understanding of how nanostructuring of the pore-filling medium in solvent- and surfactant-filled mesoporous materials governs the mass transport and surface interactions of incorporated reagents and analytes. The dependence of molecular confinement on dye charge and structure was also explored in this dissertation. The confined translational and orientational motions of a series of four different PDI dyes diffusing along one dimension (1D) within individual cylindrical silica mesopores were investigated in these studies. Specifically, the motions of cationic and anionic PDI dyes were compared to those of two uncharged PDIs having different alkane tail lengths. All four dyes exhibited populations that were immobile, along with separate populations that diffused in either 1D or 2D. The anionic and cationic PDI dyes exhibited the largest and smallest populations, respectively, of immobile molecules, suggesting that electrostatic interactions between the charged dyes and the cationic surfactant head groups play a significant role in limiting molecular motion. The cationic and anionic PDI dyes also exhibit the largest populations of 2D diffusing molecules, suggesting they may more readily pass between the cylindrical micelles and through the silica pore walls. All four dyes also emit strongly polarized fluorescence as they move in 1D, indicating they are orientationally confined within the nanochannels. Nile Red dye was used to determine the dielectric constant, ε, of nonpolar microenvironments in double-stranded DNA (ds-DNA) single molecules both in aqueous buffer solution and when adsorbed on amine-modified chemical gradient surfaces. The value of ε within the DNA decreased with increasing buffer concentration. Values of ε ∼ 6.75 and ∼3.00 were obtained in 0.1 mM phosphate buffered saline (PBS) and in 10 mM PBS, respectively. Similar effects were observed upon adsorption to chemically graded amine-modified silica surfaces. Under 1 mM buffer, ε was measured to be ∼2.84 and ∼1.90 at the low amine (high silica), and high amine (low silica) ends of the gradient, respectively. An increase in the buffer concentration again led to a decrease in ε, but only at the low amine end. It is concluded that high buffer concentrations and binding to an amine surface cause condensation of the ds-DNA, forming less polar microenvironments within its structure. These results provide important knowledge of the factors governing the polarity of DNA microenvironments to which intercalators bind.
Keywords: Mesoporous; Silica; Nile red; Fickian diffusion; Anomalous diffusionSingle molecule tracking